2020
DOI: 10.1080/1540496x.2020.1790353
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Air Quality: Evidence from China

Abstract: To test the impact of the COVID-19 pandemic on air quality, this article matches the city-level real-time air quality monitoring data with the big data on population migration provided by Baidu. The article uses urban samples from the same data sample of the Chinese lunar calendar in 2019 to construct the counterfactual status of the COVID-19 pandemic. Then, the difference-indifferences (DID) model is employed to estimate the impact of the COVID-19 pandemic on air quality. It is found that the COVID-19 pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 33 publications
4
50
0
Order By: Relevance
“…However, an analysis based on the above assumption can give us some indication of the comparative pollutant concentration and insights of air quality during the COVID-19 lockdown in 2020. This method of comparing the “control” group and “treatment” group was used by most authors such as [ 3 , 5 , 7 , 8 , 9 , 11 , 13 , 15 ]. However, as Zangari et al (2020) [ 19 ] pointed out, recently the improvement trend in air quality before and after the lockdown could also be due to other factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an analysis based on the above assumption can give us some indication of the comparative pollutant concentration and insights of air quality during the COVID-19 lockdown in 2020. This method of comparing the “control” group and “treatment” group was used by most authors such as [ 3 , 5 , 7 , 8 , 9 , 11 , 13 , 15 ]. However, as Zangari et al (2020) [ 19 ] pointed out, recently the improvement trend in air quality before and after the lockdown could also be due to other factors.…”
Section: Methodsmentioning
confidence: 99%
“…Brimblecombe et al (2021) [ 3 ] also used the air quality data NO 2 and PM 2.5 during the lockdown period in 2020 and in the previous year in 2019 in Sydney to statically compare them and reported that the daily average levels of these pollutants decreased slightly but are statistically insignificant. Ming et al (2020) [ 9 ] used air quality data in many cities across China and travel data from the Baidu website to study the air quality effect from the lockdown in China during the Lunar New Year and COVID-19 pandemic period. They reported a reduction of about 7 µg/m 3 of PM 2.5 during the pandemic lockdown across China.…”
Section: Introductionmentioning
confidence: 99%
“…The trade forecast among the major trading countries further Shows a decline until December 2020. However, it is worth mentioning that amid the COVID-19 pandemic, there is a significant improvement in air quality, though temporarily, and a positive macroeconomic response has been seen in some countries such as China and India during the COVID-19 outbreak (Ming et al, 2020). The impact on global economies and loss of millions of jobs have been one of the major causes of stress and anxiety among global populations.…”
Section: Introductionmentioning
confidence: 99%
“…; air quality (Ming et al 2020); insurance (Wang et al 2020); macroeconomy (Walmsley, Rose, and Wei 2020) trade (Vidya and Prabheesh 2020); labour market response (Yu et al…”
mentioning
confidence: 99%